Features of the Use of Personal Protective Equipment in the Foci of a New Coronavirus Infection - A. A. Kuzin; A. P. Yumanov; A. A. Degtyarev; G. G. Eremin (Эпидемиология и вакцинопрофилактика)
Relevance. In the context of the new SARS-CoV-2 coronavirus pandemic, the range of use of personal protective equipment (hereinafter referred to as PPE) is becoming increasingly broad, from emergency and emergency medical teams that go to patients with suspected COVID-19, to specialized covid hospitals. Aim. Identification of features in the operation of PPE in a strict anti-epidemic regime and development of recommendations on the use of PPE to improve the efficiency of medical professionals. Materials and methods. In the period from April to May 2020 in the field hospital of the Association of Alpine shooters at the exhibition centre, FIERA DI BERGAMO Italian Republic (hereinafter - the hospital), 8 medical and nursing teams, each of them included the doctors-epidemiologist, anesthesiologist-resuscitation, general practitioner, and nurse anesthetist (total number 32 professionals) conducted relevant sanitary-antiepidemic (preventive) and treatment-and-prophylactic interventions among patients with clinical manifestations of COVID-19. Conclusion. As a result of using a whole range of disposable PPE of various modifications, the features and disadvantages of their operation in the field were established. The main recommendations for using PPE when working with patients infected with SARS-CoV-2 are formulated.